THE ANALYSIS OF COSTA AND KALLICK'S HABITS OF MIND ON THE STUDENTS OF PROSPECTIVE BIOLOGY TEACHERS - Gloria, Ria Yulia; Sudarmin, Sudarmin; Wiyanto, Wiyanto; Indriyanti, Dyah Rini (Unnes Science Education Journal, 2017)
Habits of mind were most important to be had by the science education the students. The prospective science teachers were required to have the skills of self-regulation, creative thinking and critical thinking. Those three skills were the categories of habits of mind. This study reviewed on how the habits of mind of the students of prospective Biology teachers were, in which category the students' habits of mind were, how the differences of the habits of mind of the male and female the students were, and whether there was any relation between the students' grade points and their habits of mind. The analysis result obtained that 79.7% the students included in the adequate category of habits of mind (N=133). From 16 categories of the habits of mind, the responding with wonderment and awe category had the biggest average score that was 5.69 which meant that most of Science education the students had high enough curiosity in the mystery of the nature. There was no difference of the habits of mind had by the male and female the students, and there was no correlation between the habits of mind and the students' grade points.